ANALISIS FAKTOR-FAKTOR DALAM PERSPEKTIF FRAUD TRIANGLE SEBAGAI PREDIKTOR FRAUDULENT FINANCIAL REPORTING - Utama, I Gusti Putu Oka Surya; Ramantha, I Wayan; Badera, I Dewa Nyoman (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.07.NO.01.TAHUN 2018DO - 10.24843/EEB.2018.v07.i01.p09, 2018)
The reduction of financial reporting information’s quality is caused by management fraud behavior by manipulate the financial reporting in order to looks good. This research aims to obtain empirical evidence the effect of fraud triangle factors are financial stability, external pressure, personal financial need, financial targets, nature of industry, ineffective monitoring, organizational structure, and auditor switching to fraudulent financial reporting in nonfinancial companies which listed in Indonesia Stock Exchange period 2012-2014. The sample determined by utilizing purposive sampling technique, therefore as many as 156 of observation sample was obtained. The data observed by logistic regression analysis method. The results show that pressure element these are financial stability , external pressure , and personal financial need has a positive effect to fraudulent financial reporting. Opportunity element these are organizational structure has a negative effect to fraudulent financial reporting. Rationalization element, auditors switching has a positive effect to fraudulent financial reporting. Meanwhile financial targets , nature of industry , and ineffective monitoring have no effect.